Young adults with cystic fibrosis have altered trabecular microstructure by ITS-based morphological analysis. Issue 8 (August 2016) - Putman, M.; Greenblatt, L.; Sicilian, L.; Uluer, A.; Lapey, A.; Sawicki, G.; Gordon, C.; Bouxsein, M.; Finkelstein, J.
Abstract Summary Young adults with cystic fibrosis have compromised plate-like trabecular microstructure, altered axial alignment of trabeculae, and reduced connectivity between trabeculae that may contribute to the reduced bone strength and increased fracture risk observed in this patient population. Introduction The risk of fracture is increased in patients with cystic fibrosis (CF). Individual trabecular segmentation (ITS)-based morphological analysis of high-resolution peripheral quantitative computed tomography (HR-pQCT) images segments trabecular bone into individual plates and rods of different alignment and connectivity, which are important determinants of trabecular bone strength. We sought to determine whether alterations in ITS variables are present in patients with CF and may help explain their increased fracture risk. Methods Thirty patients with CF ages 18–40 years underwent DXA scans of the hip and spine and HR-pQCT scans of the radius and tibia with further assessment of trabecular microstructure by ITS. These CF patients were compared with 60 healthy controls matched for age (±2 years), race, and gender. Results Plate volume fraction, thickness, and density as well as plate-plate and plate-rod connectivity were reduced, and axial alignment of trabeculae was lower in subjects with CF at both the radius and the tibia (p  < 0.05 for all). At the radius, adjustment for BMI eliminated most of these differences. At the tibia, however, reductions in plate volume fraction and number, axially aligned trabeculae, and plate-plate connectivity remained significant after adjustment for BMI alone and for BMI and aBMD (p  < 0.05 for all). Conclusions Young adults with CF have compromised plate-like and axially aligned trabecular morphology and reduced connectivity between trabeculae. ITS analysis provides unique information about bone integrity, and these trabecular deficits may help explain the increased fracture risk in adults with CF not accounted for by BMD and/or traditional bone microarchitecture measurements.